2005
DOI: 10.1111/j.1525-139x.2005.18106.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Management of Valproic Acid Toxicity: A Case Report and Review of the Literature

Abstract: The incidence of intentional or accidental valproic acid (VPA) overdose is increasing. Severe VPA toxicity may lead to coma and death. Traditionally the treatment of patients with VPA toxicity has been limited to supportive measures. VPA is highly protein bound and therefore it is considered not to be removable by extracorporeal means. However, studies of VPA toxicokinetics indicate that at blood levels that exceed therapeutic concentrations, VPA protein binding sites become saturated, leading to increased con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Moreover, CVVHDF following in-series haemodialysis and haemofiltration has been shown to prevent postdialytic rebound whilst first optimising drug clearance in a case of severe VPA toxicity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CVVHDF following in-series haemodialysis and haemofiltration has been shown to prevent postdialytic rebound whilst first optimising drug clearance in a case of severe VPA toxicity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the importance of careful monitoring and dosage adjustments in the treatment of pediatric epilepsy using VPA. 47…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the importance of careful monitoring and dosage adjustments in the treatment of pediatric epilepsy using VPA. 47 Furthermore, VPA acts as a hepatic enzyme inhibitor, and its plasma concentration can be affected by concomitant medication. Studies have shown that the concurrent use of AEDs such as CBZ, phenobarbital, phenytoin, and OXC can accelerate VPA metabolism through enzyme induction, increase its clearance rate, shorten its half-life, expand its distribution volume, and reduce its plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In Case 1, the clinician urgently opened central venous access and performed CRRT+HP treatment to rapidly and stably reduce the concentration of free sodium valproate in the patient's blood. After 10 h of CRRT+HP treatment, the blood concentration of sodium valproate decreased from 635.77 mg/L to 193.00 mg/L, and the blood concentration rebounded to 263.20 mg/L after 12 h. The blood concentration of sodium valproate may rebound after one time of blood purification, 19 because drug concentration in tissues and organs is still significant, drug redistribution increases blood drug concentration again. The protein binding rate of sodium valproate is high.…”
Section: Discussionmentioning
confidence: 99%